2014
DOI: 10.3109/10903127.2014.942476
|View full text |Cite
|
Sign up to set email alerts
|

Double Sequential External Defibrillation in Out-of-Hospital Refractory Ventricular Fibrillation: A Report of Ten Cases

Abstract: Background. Ventricular fibrillation (VF) is considered the out-of-hospital cardiac arrest (OOHCA) rhythm with the highest likelihood of neurologically intact survival. Unfortunately, there are occasions when VF does not respond to standard defibrillatory shocks. Current American Heart Association (AHA) guidelines acknowledge that the data are insufficient in determining the optimal pad placement, waveform, or energy level that produce the best conversion rates from OOHCA with VF. Objective. To describe a tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 17 publications
1
30
0
Order By: Relevance
“…A retrospective case series of 10 patients with out-of-hospital DSD successfully broke refractory VF in 7 of the 10 patients after a range of 6-11 single shocks. 11 None of the 10 patients, however, survived to hospital discharge. An ED-based case report in 2014 described a male with refractory VF successfully treated with DSD.…”
Section: Discussionmentioning
confidence: 95%
“…A retrospective case series of 10 patients with out-of-hospital DSD successfully broke refractory VF in 7 of the 10 patients after a range of 6-11 single shocks. 11 None of the 10 patients, however, survived to hospital discharge. An ED-based case report in 2014 described a male with refractory VF successfully treated with DSD.…”
Section: Discussionmentioning
confidence: 95%
“…22 To date, the only published data on double sequential defibrillation in the prehospital environment have been case series and case reports. [22][23][24] The current study is the first to compare the outcomes of standard therapy and dual defibrillation in the out-ofhospital setting.…”
Section: Discussionmentioning
confidence: 99%
“…In 2015, Cabañas reported on 10 cases of refractory VF treated with double-axis external defibrillation in the prehospital setting. Three of these patients had return of spontaneous circulation (ROSC), but none survived to discharge with their protocols 10. Although the guidelines call for no higher than 200J of biphasic energy and 360J of monophasic energy, multiple studies have shown no ill effects with higher dose shocks, even as high as 720 J (monophasic) delivered using two defibrillators 9…”
Section: Discussionmentioning
confidence: 99%